Case series: Effects of a ketogenic diet on cardiometabolic health in seven outpatients with bipolar disorder - Schreel, Louis; Bürkle, Maxi; Thiem, Andrea; von Baehr, Volker; Sauren, Joshua; Keferstein, Gerrit (Frontiers in Nutrition, 2025)
BackgroundRecent research suggests that the ketogenic diet (KD) has the potential to serve as an effective treatment option for neuropsychiatric disorders, targeting both dysfunctions in brain metabolism and cardiometabolic comorbidities. In many patients, KDs may ameliorate comorbidities such as obesity, metabolic syndrome and type 2 diabetes. However, the long-term effects of KDs on cardiovascular health remain an important topic of investigation, due to considerable inter-individual variability in how KDs may impact lipid metabolism. While some studies have shown no significant change in cholesterol levels, and some have shown improvements, still others have highlighted the potential of KDs to induce or exacerbate hyperlipidemia.ObjectiveTo shed new light on this ongoing controversy, we present both beneficial and concerning effects of a 3-month intervention with Ketogenic Metabolic Therapy (KMT) (1.5:1 ratio) on a wide range of cardiometabolic health markers in seven outpatients with bipolar disorder and comorbid dyslipidemia.MethodsCardiometabolic assessments were based on markers of lipoprotein burden, such as apolipoprotein B (apoB), lipoprotein (a) (Lp(a)), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), triglyceride (TG) and total cholesterol (TC), markers of inflammation, such high-sensitivity C-reactive protein (hsCRP) and tumor necrosis factor (TNF-α), markers of oxidative stress, such as malondialdehyde-modified LDL (MDA-LDL) and nitrotyrosine, molecules that relate to endothelial function, such as homocysteine and advanced glycation end products (AGE), and anthropometric measures, such as BMI and fat mass. Mean changes between pre-KMT and post-KMT measurements were calculated. In addition, within-person changes in outcomes of interest were visually summarized using boxplots.ResultsBeneficial cardiometabolic effects included a decrease in mean Lp(a) of 6.6 mg/dl (−21%), a reduction in mean triglyceride of 40.6 mg/dl (−30%), a reduction in mean apoB of 0.14 g/L (−10,5%) and an increase in mean HDL-C of 3 mg/dL (+5%), a reduction in mean hsCRP of 0.94 mg/L (−45%), a reduction in mean TNF-α of 1.31 pg/ml (−7%), a reduction in mean MDA-LDL of 36.77 U/L (−38%), a reduction in mean nitrotyrosine of 225 nmol/L (−28%), a mean weight reduction of 4 kg (−4,6%), a mean visceral fat reduction of 0.69% (−10%) and a mean fat mass reduction of 3.7 kg (−12%). However, some concerning effects were also observed. Of note, mean homocysteine levels increased by 1.94 umol/L (+18%) and mean AGE levels increased by 30.9 ug/ml (+106%). Moreover, mean LDL-C was increased by 14 mg/dl (+9%) and mean total cholesterol was increased by 7 mg/dl (+3%).ConclusionBased on these findings, it is concluded that comprehensive Ketogenic Metabolic Therapy provided to outpatients with bipolar disorder can be beneficial in improving a broad range of cardiometabolic health markers, including lipid metabolism, inflammation, oxidative stress and anthropometric measures. Tentatively, these findings suggest that at least a proportion of patients with bipolar disorder may find remarkable improvements in cardiometabolic health adopting a metabolic treatment such as the ketogenic diet. However, potentially concerning effects on markers such as homocysteine and AGE call for well-formulated, individualized KDs.